Manfaat Pelepah Sebagai Sumber Bahan Organik Pada Media Tanam Kelapa Sawit - Mira Ariyanti (Paspalum: Jurnal Ilmiah Pertanian, 2021)
Palm midrib is a part of the oil palm plant that is pruned with a specific pruning cycle in oil palm plantations. The pruned oil palm midribs are usually only piled around dead wicket of oil palm as a mulch which will naturally decompose. It takes a long time for the palm midrib mulch to be decomposed completely. If not managed properly, oil palm midribs mulch can become garden waste, therefore a good handling method is needed, for example by making it as compost. The use of oil palm midribs as compost is associated with both macro and micro nutrient content and the presence of certain growth hormones. Oil palm midrib compost can be used as a compost mix for planting media in oil palm nurseries and as a measure to make inorganic fertilizers more efficient. In addition, during the immature plants, compost of oil palm midribs can also be applied together with various mixtures such as humic acid and biological fertilizers. Oil palm midrib compost as part of the plant is alleged to be the best source of organic material for meeting plant nutrient needs.